IMPLEMENTATION OF GROUP COUNSELING MODELING TECHNIQUES IN REDUCING AGGRESSIVE BEHAVIOR IN ADOLESCENTS IN CUNGKINGAN HAMLET: IMPLEMENTASI KONSELING KELOMPOK TEKNIK MODELING DALAM MEREDUKSI PERILAKU AGRESIF PADA REMAJA DUSUN CUNGKINGAN - Umi Bariroh; Heriberthus Wicaksono; Agus Mursidi (Program Studi Bimbingan dan Konseling, 2025)
This research aims to (1) find out if group counseling modeling techniques are effective in reducing aggressive behavior in Cungkingan Hamlet teenagers. (2) Knowing the differences between the group that received treatment and the group that did not receive treatment. This research uses a Non Equivalent Pretest-Posttest Control Group Design. The population of this study was 30 respondents. The sample for this research was 8 respondents divided into two groups, namely, 4 experimental groups and 4 control groups. Data analysis for this research uses correlated statistical paired sample t-test data and uncorrelated statistical analysis of paired sample t-test data. The research results show that: (1) Modeling technique group counseling is effective in reducing aggressive behavior in Cungkingan Hamlet teenagers with results (24,592 > 1,753) meaning that based on decision making Ho is rejected Ha is accepted. (2) There is a difference between the experimental group that received treatment and the control group that did not receive treatment in reducing aggressive behavior in adolescents with results (10,683≠5,358)